The concept of Quranic dialogue and its function in the Quranic story . Surat Al-Kahf as a model - hofaf, louiza (El Omda in Linguistics and Discourse Analysis, 2024)
Dialogue is an important and essential element in the narative process , and its effectiveness is evident in adding a kind of vitality to the narrative text , as it is what takes places between the characters in terms of conversation that convey their emotions and feelings as well as their differnt positions .The truth of the character , its goals , how it moves and its management of the event in the narrative text, so that the recipient can perceive the features and emotions of the interlocutors, through the description and depiction performed by the Quranic dialogue with great precision and ingenuity, not to mention the element of suspense that contributes to the readers tention and adherence to the thread of divine storytelling for fun and interest together.